Σχεδιασμός συστήματος αναβατορίου για γενική χρήση σε πολυκατοικίες - Ιωακείμ, Λοΐζος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
This work pertains to the design of an elevator for generic use in a three-story building.Through relevant computations and a judicious design selection the design of the elevator system is implemented, the key objective being passenger safety during operation.Four preliminary designs were assessed before the final decision was made. The aforementioned design methodology entailed detailed calculations pertinent to the volume and mass of the frame, design of the wire ropes, determination of the nominal weight and counterweight of the elevator, appropriate selection of the friction pulley to be used, determination of the requisite power rating of the driving motor, selection of the appropriate speed reducer, sizing of the shaft and chamber etc.Subsequently, the design drawings of the final design were properly implemented using AutoCaD 2011 and presented in a standard engineering format which included orthographic and isometric projections.The report finally presents the conclusions drawn from the design project.
Keywords: Εlevator; Εlevator system-Design; Αναβατόριο; Σύστημα ανελκυστήρα-Σχεδιασμός